The Role of Non-Verbal Communication in Asynchronous Talk Channels ‎ - Josiah Zhan Xiong Koh; Tara Hulbert (Flexible Learning Association of New Zealand, 2023)
With the increased adoption of online learning (even greater as a result of the COVID-19 pandemic), online asynchronous discussions have become a mainstay of many online learning platforms. As teachers struggle to communicate and connect with students due to the forced transition online, we can better appreciate the differences between traditional nonverbal communication in a face-to-face environment and that of online nonverbal communication. Because digital literacy underpins the whole online learning experience, and because nonverbal communication (NVC) cues such as body language and paralanguage are not visible in asynchronous text-based online learning, this paper presents the relationship (if any) between electronic nonverbal communication (eNVC) and teaching/social presences and digital literacy, as well as its role in student motivation and engagement. A correlational study was conducted using surveys to gather data from 88 Level 5 Business Area students. The data was analysed using a Pearson's correlation analysis. The study has found that there is a correlation between eNVC and the social/teaching presence and digital literacy in the asynchronous online discussions, and that eNVC is related to teaching and social presences, but not to digital literacy.